PENGARUH ENTREPRENEURSHIP TERHADAP PENANGGULANGAN PENGANGGURAN MELALUI PEMBERDAYAAN MASYARAKAT DI PALEMBANG - Margahana, Helisia (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
ABSTRACT: Entrepreneurship is a social phenomenon that has grown rapidly in efforts to solve and overcome various social problems, such as economic improvement and poverty alleviation and unemployment. This study aims to describe the role of community empowerment and entrepreneurship in building a community economy that has implications for unemployment reduction. In tackling unemployment cannot be carried out only on the basis of commitment and determination, desire for responsibility, obsession of opportunity, tolerance of risk, ambiguity, and uncertainty, self-confidence, creativity and flexibility, desire for direct feedback, high energy, motivation to excel, future orientation, willingness to learn from failure, and leadership abilities, but must be accompanied by providing entrepreneurial skills, entrepreneurial opportunities, marketing orientation and networking from the community itself. So that the target of unemployment reduction will be achieved, namely the creation of employment opportunities, increased community income, and social cohesion and inclusive economic growth. Based on the conclusions, some suggestions can be given including increasing the number of social entrepreneurial actors who play an active role in improving the economic community in order to reduce unemployment and poverty. The role and cooperation with the government in combating unemployment is highly expected and more evident in its implementation.Keywords: Entrepreneurship, Empowerment, Unemployment Mitigation